Economics Growth, Income Distribution, and Poverty in Central Java - Hariadi, Pramono (Economic Journal of Emerging Markets, 2011)
Among the central issues in policy making are poverty alleviation and increasing income distribution. This paper measures the impact of economic growth on income inequality and poverty alleviation, namely whether income inequality becomes trade-off for poverty alleviation in 35 Central Java regencies. The paper uses fixed effect model by weighting cross section weights. The results show that economic growth increases income inequality. Furthermore, economic growth alleviates poverty and increases income inequality, but the effect is smaller than the reduction in poverty. Therefore, the increased income inequality is not a trade off to poverty alleviation and the economic growth is effective to alleviate poverty. Keywords: Economic growth, income inequality, poverty alleviation